Fatigue design of sintered steel components: effect of stress concentrations and mean stresses on local strength using highest stressed volume approach. (December 2013) - Lipp, K.; Baumgartner, J.; Beiss, P.
<x content-type="archive" xml:space="preserve">Abstract</x> The increasing implementation of sintered steel parts for highly loaded engine and gear box applications is accompanied by the need for reliable fatigue design, especially in the pre-development phase. In most cases necessary characteristic values for the fatigue design of PM components, especially for sharply notched areas, are not available. In the present study, the locally endurable stress amplitude for different loading modes and mean stresses is derived for a diffusion alloyed 4%Ni sintered steel (Distaloy AE) via the highly stressed volume approach. The correlation of the locally endurable stress amplitude with the highly stressed volume, defined as Vx, is estimated for x = 80% and 90%, to evaluate both approaches with regard to PM steels. The applicability of assessing local cyclic behaviour by the highly stressed volume approach is demonstrated for a typical design detail of a highly loaded PM part. Characteristic values for the fatigue design of PM components are recommended.